Accessibility Analysis of Learning Management System Websites - Dwi Fithriyaningrum; Kusumawardani, Sri Suning; Wibirama, Sunu (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2022)
In the digital era, Learning Management System is widely used to spread information in higher education, particularly at the university level. There are, however, issues with the Learning Management System's accessibility for users with disabilities. This research aims to investigate the accessibility issues of learning management websites of 30 universities in Indonesia. The top 30 universities in Indonesia according to Webometrics 2022 are the basis for this study. Accessibility issues will be identified and examined using the Wave evaluation tool which is in accordance with the Web Content Accessibility Guidelines 2.1 used by ISO 40500. Web Content Accessibility Guideline 2.1 has principles that any web should follow: Perceivable, Operable, Understandable, and Robust. Based on the research findings, The low contrast ratio between text and background, the absence of text explanations in the images, the lack of descriptive text on the links, the absence of text labels on the form, and the absence of text description on the button were the most frequently encountered accessibility issues.